Nuclear structure and direct reaction studies in particle-γ coincidence experiments at the FSU John D. Fox superconducting linear accelerator laboratory - Spieker, Mark-Christoph; Almaraz-Calderon, Sergio (Frontiers in Physics, 2024)
Since its foundation in the 1960s, the John D. Fox Superconducting Linear Accelerator Laboratory at Florida State University (FSU) pursued research at the forefront of nuclear science. In this contribution, we present recent highlights from nuclear structure and reaction studies conducted at the John D. Fox Superconducting Linear Accelerator Laboratory, also featuring the general experimental capabilities at the laboratory for particle-γ coincidence experiments. Specifically, we focus on light-ion induced reactions measured with the Super-Enge Split-Pole Spectrograph (SE-SPS) and the CATRiNA neutron detectors, respectively. Some results obtained with the CeBrA demonstrator for particle-γ coincidence experiments at the SE-SPS are presented. A highlight from the first experimental campaigns with the combined CLARION2-TRINITY setup, showing that weak reaction channels can be selected, is discussed as well.